2022
DOI: 10.1108/ijoa-01-2022-3100
|View full text |Cite
|
Sign up to set email alerts
|

Employee proactivity and proactive initiatives towards creativity: exploring the roles of job crafting and initiative climate

Abstract: Purpose Although previous research has shown that proactive initiatives are mostly related to performance- and creativity-related outcomes, the questions of “how” and “when” proactivity brings about creativity are not still fully answered. This conceptual investigation aims to explain the intervening role of job crafting by conceptualising it as a behavioural mechanism that employees engage in to increase their functioning. Besides, this study examines initiative climate as a contextual factor that shapes this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 62 publications
2
5
0
Order By: Relevance
“…This means that taking the initiative at work helps one to realize entrepreneurial goals, which ultimately benefit the enterprise. The finding is similar to that of Kilic and G€ ok (2022) who found out that one's proactive orientation like taking an initiative turns into enacting creativity in work processes. The finding is also similar to that of Fay et al (2022) who indicated that when individuals foresee themselves as engaging in proactive work behavior, they rate their work as more meaningful and increase their performance.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This means that taking the initiative at work helps one to realize entrepreneurial goals, which ultimately benefit the enterprise. The finding is similar to that of Kilic and G€ ok (2022) who found out that one's proactive orientation like taking an initiative turns into enacting creativity in work processes. The finding is also similar to that of Fay et al (2022) who indicated that when individuals foresee themselves as engaging in proactive work behavior, they rate their work as more meaningful and increase their performance.…”
Section: Discussionsupporting
confidence: 85%
“…This means that taking the initiative at work helps one to realize entrepreneurial goals, which ultimately benefit the enterprise. The finding is similar to that of Kilic and Gök (2022) who found out that one's proactive orientation like taking an initiative turns into enacting creativity in work processes. The finding is also similar to that of Fay et al .…”
Section: Discussionsupporting
confidence: 85%
“…We can further stress that as well as CJC is an effective way of optimizing AWB, the affective states may also determine daily CJC initiatives. In addition, examining the mutual interaction between behavioral and cognitive forms of crafting may be a potential avenue for further investigations (Kilic and Gök, 2022; Melo et al , 2021). Finally, although there have been reverse approaches in the literature (Romeo et al , 2020), we underline that CJC should be considered as an initial step for the behavioral initiatives of the job crafting process (Berg et al , 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The moderating effect of proactive behaviour Employees who engage in proactive organizational behaviours are involved in change actions in their work environment (Griffin et al, 2007). An employee who engages in proactive behaviour is recognized as having a proactive personality, which is reflected in a willingness to take responsibility for constructive change (Fuller et al, 2006) and for creativity (Kilic and Gök, 2022). Numerous factors affect job satisfaction.…”
Section: Servant Leadership and Job Satisfactionmentioning
confidence: 99%